2003
DOI: 10.1086/373997
|View full text |Cite
|
Sign up to set email alerts
|

ExperimentalPneumocystis cariniiPneumonia in Simian Immunodeficiency Virus–Infected Rhesus Macaques

Abstract: To establish experimental Pneumocystis carinii infection in simian immunodeficiency virus (SIV)-infected macaques as a model of acquired immunodeficiency syndrome (AIDS)-associated P. carinii pneumonia (PCP), SIV-infected macaques were inoculated intrabronchially with macaque-derived P. carinii, and P. carinii-specific polymerase chain reaction (PCR) and flow cytometric analysis of bronchoalveolar lavage fluid were done biweekly for up to 44 weeks after inoculation. All inoculated animals had a P. carinii-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
80
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(84 citation statements)
references
References 49 publications
2
80
2
Order By: Relevance
“…In laboratory rodents, nested PCR of oral swabs has demonstrated that close to 100% of adult rats are colonized with Pneumocystis shortly after receipt (127). Similarly, spontaneous colonization occurs in both free-living and laboratory nonhuman primates (23,44,63). In a free-living macaque colony, all animals had detectable colonization at some point over a 2-year observation period, and the duration of colonization averaged 2 months (63).…”
Section: Colonization In Animalsmentioning
confidence: 99%
“…In laboratory rodents, nested PCR of oral swabs has demonstrated that close to 100% of adult rats are colonized with Pneumocystis shortly after receipt (127). Similarly, spontaneous colonization occurs in both free-living and laboratory nonhuman primates (23,44,63). In a free-living macaque colony, all animals had detectable colonization at some point over a 2-year observation period, and the duration of colonization averaged 2 months (63).…”
Section: Colonization In Animalsmentioning
confidence: 99%
“…Recently, our laboratory has developed an experimental model of Pneumocystis infection in rhesus macaques (4). In these studies, Pneumocystis was introduced intrabronchially, and the progression of infection was monitored by Pneumocystis-specific PCR of BAL fluid (4).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory has developed an experimental model of Pneumocystis infection in rhesus macaques (4). In these studies, Pneumocystis was introduced intrabronchially, and the progression of infection was monitored by Pneumocystis-specific PCR of BAL fluid (4). In addition to its usefulness as a diagnostic probe, the sequence variability at the mt LSU locus allows for the distinction between the presence of the inoculating strain and a naturally acquired infection in this model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations